The Antitumoral Effect of Paris Saponin II on Head and Neck Squamous Cell Carcinomas Mediated via the Nitric Oxide Metabolic Pathway - Qi, Wenwen; Zhu, Fangyuan; Wang, Min; Teng, Zhenxiao; Xu, Runtong; Xi, Yue; Meng, Qiu; Wu, Xinhao; Zhao, Hui; Ma, Min; Hou, Xiaozhi; Wang, Baowei; et al. (Frontiers in Cell and Developmental Biology, 2022)
Paris saponin has shown great therapeutic value in cancer therapy. We used isolated Paris saponinII (PSII), an active component of Paris saponin, and demonstrated its anti-tumor effect on human head and neck squamous cell carcinoma cell lines. Additionally, we investigated its mechanisms of action in vivo by establishing xenograft mouse model. The results showed that PSII had presented strong anticancer effects on both a hypopharyngeal malignant tumor cell line (FaDu) or in Laryngeal carcinoma cell lines (Tu212 and Tu686). In addition, we successfully isolated and cultured the head and neck squamous stem cells and the primary fibroblasts to perform metabonomics studiies. The results showed that RPII remarkably decreased energy metabolism, and the type III nitric oxide synthase 3 (NOS3) may be a target to block the tumor growth. Furthermore, we found that PSII inhibited HNSCC proliferation and metastasis by inhibitting the nitric oxide metabolic pathway. Overall, these results demonstrated that PSII is a potent anticancer agent,and the metabonomics analysis is a valuable tool to investigate and estiblish the antitumor effects of traditional Chinese medicines.